2008
DOI: 10.5650/jos.57.503
|View full text |Cite
|
Sign up to set email alerts
|

Triazole-linked Host Compounds for Chiral-Discrimination toward Amino Acid Ester Guests

Abstract: The chiral-discriminating abilities of new triazole-linked host compounds (6, 7) toward amino acid esters were evaluated by the FABMS/EL-guest method. Two types of host appending saccharide derivatives were synthesized by the copper-catalyzed Huisgen-1,3-dipolar cycloaddition (CuAAC). Host compounds binding constants and chiral-discriminating abilities toward the enantiomeric alanine esters were evaluated by UV method in chloroform. The structural requirements of triazole-linked hosts were determined by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For instance, triazole-linked hosts have been used for chiral discrimination of enantiomeric alanine esters. 8 Cholic acid oligomers with 1,2,3-triazole groups have been used as chemosensors for the detection of trace amounts of metal ions.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…For instance, triazole-linked hosts have been used for chiral discrimination of enantiomeric alanine esters. 8 Cholic acid oligomers with 1,2,3-triazole groups have been used as chemosensors for the detection of trace amounts of metal ions.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…Then, the chiral analyte (guest) reacts with the host molecules to form a diastereomeric mixture, which will simultaneously produce both labeled and unlabeled molecular ion peaks on the mass spectrum. 29 And an analysis was also performed to examine the ability of 7 chiral m-methyl-substituted polysaccharides to distinguish chiral alcohols. Fast atom bombardment (FAB), matrix-assisted laser desorption/ionization mass spectrometry, and electrospray ionization (ESI) can be used as soft ionization techniques.…”
Section: Host-guest (H-g) Associationmentioning
confidence: 99%
“…It was found that the oligosaccharides of the β-cello series had a high stereoselectivity to the S-tryptophan ammonium salt. 29 And an analysis was also performed to examine the ability of 7 chiral m-methyl-substituted polysaccharides to distinguish chiral alcohols. 30 Grigorean explored the interaction between 18-crown-6-tetracarboxylic acid and amino acids with enantiomer-labeled guest method to understand more deeply the enantiomeric recognition phenomena.…”
Section: Host-guest (H-g) Associationmentioning
confidence: 99%
“…(Chart 5). Sato et al [83] synthesized the new triazole linked hosts, (193,194) (Figure 17) by versatile, rapid and high yield copper catalyzed Huisgen-1,3-dipolar cycloaddition (Click Chemistry) of linker azide with saccharide alkyne. These two compounds, 193, 194 then were investigated for the chiral recognition ability.…”
Section: Triazole Ring Containing Receptorsmentioning
confidence: 99%